The effectiveness of technical vocational education and training to employability of TVET-STEP Graduates in City of Manila - Bañaga, Mark Joven V., Bulaong Lyra Mae G., Labnotin, Brendalyn R., Moog, Franck Jeremy B., Ramo, Ma. Stephanie R., Regner, Nicole Anne L., Reyes, Ednalynne T., Saddi, Kurt Basty S., Sumampong, Lyxander Zoe S., Tabien, Marion C., Zita, Klester Kim S. 4 0 16; 5
Abstract Unemployment is one of the main problems in the country. Moreover, because of the growing population and demand for jobs, the Philippines' unemployment problems are severe. To address the problem of unemployment, TESDA provides the Special Training for Employment Program (STEP) to Filipinos. The purpose of this program is to give enrollees opportunities for skill development and training as well as increase their proficiency and awareness of the abilities needed to be job ready. The main objective of the study is to determine the effectiveness of the TVET program on the employability of TVET-STEP graduates. The purpose of this study was to determine the demographic and employment profile of the respondents, TVET STEP Graduates' perception to the TVET program, and the effectiveness of the TVET program on the employability of TVET-STEP graduates in terms of job opportunities, incentives, and skill utilization. This study utilized a quantitative research design that employed a descriptive survey method through online survey questionnaires. Descriptive and inferential statistics were used to analyze the findings of the study. According to the findings, TESDA deployed the TVET program well, however, there is no significant relationship between the program, and the employability of STEP scholars.
Research Paper: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2